Chest Radiographs for Pediatric TB Diagnosis: Interrater Agreement and Utility - Kaguthi, G.; Nduba, V.; Nyokabi, J.; Onchiri, F.; Gie, R.; Borgdorff, M. (Interdisciplinary Perspectives on Infectious Diseases, 2014)
The chest radiograph (CXR) is considered a key diagnostic tool for pediatric tuberculosis (TB) in clinical management and endpoint determination in TB vaccine trials. We set out to compare interrater agreement for TB diagnosis in western Kenya. A pediatric pulmonologist and radiologist (experts), a medical officer (M.O), and four clinical officers (C.Os) with basic training in pediatric CXR reading blindly assessed CXRs of infants who were TB suspects in a cohort study. C.Os had access to clinical findings for patient management. Weighted kappa scores summarized interrater agreement on lymphadenopathy and abnormalities consistent with TB. Sensitivity and specificity of raters were determined using microbiologically confirmed TB as the gold standard (n=8). A total of 691 radiographs were reviewed. Agreement on abnormalities consistent with TB was poor; k=0.14 (95% CI: 0.10–0.18) and on lymphadenopathy moderate k=0.26 (95% CI: 0.18–0.36). M.O [75% (95% CI: 34.9%–96.8%)] and C.Os [63% (95% CI: 24.5%–91.5%)] had high sensitivity for culture confirmed TB. TB vaccine trials utilizing expert agreement on CXR as a nonmicrobiologically confirmed endpoint will have reduced specificity and will underestimate vaccine efficacy. C.Os detected many of the bacteriologically confirmed cases; however, this must be interpreted cautiously as they were unblinded to clinical features.